A combined series-elastic actuator & parallel-elastic leg no-latch bio-inspired jumping robot. (July 2020) - Hong, Chong; Tang, Dewei; Quan, Qiquan; Cao, Zhuoqun; Deng, Zongquan
Highlights: A design concept of frog-inspired no-latch jumping strategy is proposed. A symmetrical high-stroke one-DOF robotic leg mechanism is designed and analyzed. The 100.3 g prototype jumps to a height of 1.3 m with slight body rotation in the air. Simulation results of jumping performance are highly consistent with the experiments. The energy-storing capacity of the robot exceeds all the existing no-latch jumping robots. Abstract: Compared with the catapult mechanism widely employed by small jumping robots, recently proposed jumping strategies based on series-elastic actuators (SEA) without latch mechanisms perform better in terms of agility, structural robustness and maneuverability. However, in some practical applications, they have difficulty in effectively storing energy before the push-off. This paper presents a novel no-latch jumping strategy inspired by frogs, achieving highly effective energy storage. The jumping strategy combines an SEA with a parallel-elastic linkage, which allows one motor to rotate in one direction to store the elastic energy and automatically trigger its release. Combined with this strategy, a frog-inspired robotic leg mechanism is designed. The jumping process is analysed in detail and the kinematic and dynamic models are derived. Bars' dimensions and springs' parameters are determined by the optimization to maximize the energy-storing capacity. The simulation is performed to predict the jumping performance. A 100.7 g prototype is fabricated and jumps to a height of 1.3 m with slight aerial body rotation. The energy-storing capacity of the robot is 18.1 J/Kg.